Recruiting Project Managers: A Comparative Analysis of Competencies and Recruitment Signals From Job Advertisements. Issue 5 (23rd September 2013) - Ahsan, Kamrul; Ho, Marcus; Khan, Sabik
Abstract: This research addresses the competencies organizations use through project manager job advertisements. We develop a list of project manager job competencies; break down the competency components into knowledge, skills, and abilities; and conduct a comparative analysis of the use of these competencies. We examine the online contents of project manager job advertisements in the public domain. Analysis shows that industry job advertisements emphasize "soft skills" and competencies in a manner different than that in the literature. Additionally, differences are found across countries and between industries. Implications from the findings highlight the incongruent dissemination of project manager competencies, regional and industrial demands, and the recruitment of project managers.